2022
DOI: 10.3389/fmed.2022.903188
|View full text |Cite
|
Sign up to set email alerts
|

Application of Internet of Medical/Health Things to Decentralized Clinical Trials: Development Status and Regulatory Considerations

Abstract: BackgroundThe need for a new style of clinical trials, called decentralized clinical trials (DCTs), has been increasing as they do not depend on physical visits to clinical sites. DCTs are expected to provide a new opportunity to patients who cannot participate in a clinical trial due to geographical and time limitations. For the adoption of DCTs, it is essential that medical devices with Internet of Medical Things (IoMT) and Internet of Health Things (IoHT) based technologies are developed and commercially ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…A previous study reported on IoHTs that are expected to be used in DCTs through bibliographic citation network analysis and text mining. 4 The results of using clinical trial databases as the source of information are consistent with those of the previous study. As shown in table 1 , the largest number of trials with DCT components were related to diseases of the circulatory system (124 studies), followed by endocrine, nutritional and metabolic diseases (70 trials), diseases of the nervous system (61 studies) and mental and behavioural disorders (46 studies).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A previous study reported on IoHTs that are expected to be used in DCTs through bibliographic citation network analysis and text mining. 4 The results of using clinical trial databases as the source of information are consistent with those of the previous study. As shown in table 1 , the largest number of trials with DCT components were related to diseases of the circulatory system (124 studies), followed by endocrine, nutritional and metabolic diseases (70 trials), diseases of the nervous system (61 studies) and mental and behavioural disorders (46 studies).…”
Section: Discussionsupporting
confidence: 88%
“…A previous study reported on IoHTs that are expected to be used in DCTs through bibliographic citation network analysis and text mining 4. The results of using clinical trial databases as the source of information are consistent with those of the previous study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Hence, the adoption of DCTs was challenging. By February 2022, only two countries (Denmark and Switzerland) had digital clinical trials included in their guidelines 15. In-depth deliberation of the topic was initiated in 2010 with a European Medicines Agency (EMA) position paper covering electronic source data and data transcribed to electronic data collection tools and was further detailed in 2023 in the Guideline on computerised systems and electronic data in clinical trials 16.…”
Section: Introductionmentioning
confidence: 99%